Development finance; institutions, problems, and prospects - Perera, Phillips (New York : Praeger, 1968)
This book seek to examine capital environment. That is various institutional mechanisms and practices that are used to channel capital to industry, from public, private and mixed and a host of commercial and central banks. It pointed out how financial institutions in developing countries can mobilize more local savings for industries.
Bibliography: p. 439-440.
usc 09/08/18
Loans
Keywords: Finance; Developing countries